2022
DOI: 10.3390/curroncol29060306
|View full text |Cite
|
Sign up to set email alerts
|

Selective Internal Radiation Therapy with Yttrium-90 for Intrahepatic Cholangiocarcinoma: A Systematic Review on Post-Treatment Dosimetry and Concomitant Chemotherapy

Abstract: Selective internal radiation therapy (SIRT) with yttrium-90 (90Y)-loaded microspheres is increasingly used for the treatment of Intrahepatic Cholangiocarcinoma (ICC). Dosimetry verifications post-treatment are required for a valid assessment of any dose-response relationship. We performed a systematic review of the literature to determine how often clinics conducted post-treatment dosimetry verification to measure the actual radiation doses delivered to the tumor and to the normal liver in patients who underwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 79 publications
0
2
0
Order By: Relevance
“…The majority of research on the use of SIRT in CCA makes use of treatment planning that delivers a mean absorbed dose of 120 Gy to the tumor and a threshold dose of no more than 50-70 Gy to the surrounding healthy liver parenchyma [66]. Various studies have shown sizable disparities between dosimetry verification studies performed after yttrium-90 TARE and the pretreatment predictive planning marked albumin macroaggregates: These differences may result from variations in the flow dynamics, catheter position, and particle size, weight, and density [67][68][69].…”
Section: Locoregional Approachesmentioning
confidence: 99%
“…The majority of research on the use of SIRT in CCA makes use of treatment planning that delivers a mean absorbed dose of 120 Gy to the tumor and a threshold dose of no more than 50-70 Gy to the surrounding healthy liver parenchyma [66]. Various studies have shown sizable disparities between dosimetry verification studies performed after yttrium-90 TARE and the pretreatment predictive planning marked albumin macroaggregates: These differences may result from variations in the flow dynamics, catheter position, and particle size, weight, and density [67][68][69].…”
Section: Locoregional Approachesmentioning
confidence: 99%
“…Chemotherapy has been developed with an understanding of the biology and molecular mechanisms of CCA [6]. Radiotherapy has also improved with internal small, sealed sources [7,8] and proton beams [9], mainly with palliative and supportive intent. Immunotherapy has evolved and improved with the advent of immune checkpoint inhibitors, such as durvalumab (a PD-L1 antibody) [10] and CAR-T therapy [11].…”
Section: Introductionmentioning
confidence: 99%